Bomb blast shrapnel trauma to the main pulmonary artery: learning points to achieve a safe outcome. (1st October 2018) - Barnard, James; Sharman, Anna; Brazier, Andrew
Abstract: A 47-year-old patient was injured in a bomb blast and sustained trauma due to multiple fragments of shrapnel from a terrorist explosive device. We report on the surgery required to safely remove a piece of shrapnel from the anterior wall of the main pulmonary artery (PA). A chest X-ray revealed a left-sided haemothorax. A computed tomography scan confirmed the trajectory and position of a metal bolt that had lodged between the main PA and the aortic arch. At surgery, a limited left anterior thoracotomy was performed initially. A significant quantity of blood was observed in the pericardium, and the incision was extended to perform a hemi-clamshell incision with a transverse division of the sternum. Cardiopulmonary bypass (CPB) was initiated before prizing the shrapnel from a haematoma involving the front wall of the main PA. The use of the CPB prevented uncontrolled haemorrhage, and the injury to the wall was successfully repaired. The patient subsequently developed acute respiratory distress syndrome and required a prolonged period of ventilation but made a full recovery after multiple further surgeries to remove the shrapnel from his neck and legs, having been injured by 11 pieces of the shrapnel in total.